2009
DOI: 10.1037/a0016085
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of early alliance ruptures and their resolution to process and outcome in three time-limited psychotherapies for personality disorders.

Abstract: This study examined the relationship of early alliance ruptures and their resolution to process and outcome in a sample of 128 patients randomly assigned to 1 of 3 time-limited psychotherapies for personality disorders: cognitive-behavioral therapy, brief relational therapy, or short-term dynamic psychotherapy. Rupture intensity and resolution were assessed by patient- and therapist-report after each of the first 6 sessions. Results indicated that lower rupture intensity and higher rupture resolution were asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
144
2
19

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(175 citation statements)
references
References 61 publications
10
144
2
19
Order By: Relevance
“…Research has suggested that fluctuations in the quality of the alliance over the course of treatment is common, and the process of repairing strains or ruptures in the alliance has been shown to be related to therapeutic gains and positive treatment outcome (Horvath & Luborsky, 1993;Muran, 2002;Muran et al, 2009;Norcross & Wampold, 2011a, 2011bSafran, Muran, & Eubanks-Carter, 2011;Stiles et al, 2004;Strauss et al, 2006). There is now broad consensus in the literature that disruptive rupture events are important components of the therapy process, with the resolution of therapeutic conflicts a catalyst for change (Norcross & Wampold, 2011a, 2011bSafran et al, 2011;Strauss et al, 2006).…”
Section: Implications For Researchmentioning
confidence: 99%
“…Research has suggested that fluctuations in the quality of the alliance over the course of treatment is common, and the process of repairing strains or ruptures in the alliance has been shown to be related to therapeutic gains and positive treatment outcome (Horvath & Luborsky, 1993;Muran, 2002;Muran et al, 2009;Norcross & Wampold, 2011a, 2011bSafran, Muran, & Eubanks-Carter, 2011;Stiles et al, 2004;Strauss et al, 2006). There is now broad consensus in the literature that disruptive rupture events are important components of the therapy process, with the resolution of therapeutic conflicts a catalyst for change (Norcross & Wampold, 2011a, 2011bSafran et al, 2011;Strauss et al, 2006).…”
Section: Implications For Researchmentioning
confidence: 99%
“…Estes padrões cognitivos e interpessoais negativos são elementos de destaque na abordagem de Safran (e.g., 1990Safran (e.g., , 1998Safran & Segal, 1990;Safran & Muran, 2000;Safran, Muran & Proskurov, 2009;Muran, et al, 2009;Safran, Muran & Eubanks-Carter, 2011;Safran & Kraus, 2014). Intitulados "ciclos cognitivos interpessoais", são expostos, neste modelo teórico, como padrões rígidos de atuação, que limitam o individuo nas suas experiências e agem no sentido da cristalização dos modelos de relação, i.e., da inviabilização de formas alternativas (e mais adaptativas) de relacionamento (Safran, 1984(Safran, , 1990Safran & Segal, 1990;Safran & Muran, 2000;Safran, Muran & Proskurov, 2009;Muran, et al, 2009;Safran, Muran & Eubanks-Carter, 2011;Safran & Kraus, 2014).…”
Section: Os Ciclos Cognitivo-interpessoais No Contexto Da Intervençãounclassified
“…Intitulados "ciclos cognitivos interpessoais", são expostos, neste modelo teórico, como padrões rígidos de atuação, que limitam o individuo nas suas experiências e agem no sentido da cristalização dos modelos de relação, i.e., da inviabilização de formas alternativas (e mais adaptativas) de relacionamento (Safran, 1984(Safran, , 1990Safran & Segal, 1990;Safran & Muran, 2000;Safran, Muran & Proskurov, 2009;Muran, et al, 2009;Safran, Muran & Eubanks-Carter, 2011;Safran & Kraus, 2014). Estes ciclos ancoram-se, à semelhança do que os seus predecessores anteciparam, num conjunto de constrições associadas às experiências precoces com figuras significativas que, para estas pessoas, concorreram na formação de esquemas interpessoais pouco flexíveis e maladaptativos (Safran & Segal, 1990;Safran & Muran, 2000).…”
Section: Os Ciclos Cognitivo-interpessoais No Contexto Da Intervençãounclassified
“…Apesar disso, outras pesquisas revelam haver dois padrões de desenvolvimento da aliança terapêutica ao longo do tratamento: um refere-se à constância da aliança ao longo da terapia, e o outro ao crescimento linear da sua qualidade ao longo do tempo 67,68 . Por isso, torna-se necessário outras pesquisas visando contribuir para esses esclarecimentos.…”
unclassified